(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The açaí palm (Euterpe oleracea Mart.) is a tree native to the Amazonia. In some states in the region, growth of the planted area has been observed, but the difficulty in obtaining substrates which are viable for the production of seedlings is high. It was intended in a first step to evaluate the effect of seed size and substrates upon germination and in the second step, to evaluate the initial growth of seedlings of E. oleracea on different substrates. The experimental design was a completely randomized design in 2 x 2 factorial scheme with four replications at 100 seeds. Germination percentage, percentage of abnormal seedlings, shoot and root length and dry weight of the seedlings were evaluated after 70 days. In the second step, completely randomized design in 9 x 6 factorial scheme with five replications with four seedlings/ plot was utilized. At 60, 90 , 120 , 150 , 180 and 210 days after transplanting, shoot height and diameter of the stem of the plant were assessed, number of leaves were determinate at 90, 120 , 150, 180 and 210 dat and at 210 dat, determinations of dry weight of the shoot and root system were conducted. These samples were put in an oven with forced air circulation at 60 ºC for 72 hours. Açaí seeds considered large present greater germination percent as compared with small seeds and the substrate sand provides greater percentage of seed germination. The substrates composed of 75% (soil+sand) + 25% manure and with 75% (soil+sand) + 25% carbonized rice husk present better development of açai seedlings.